[University of California track and field athlete] (1901)
The athlete is wearing a sleeveless jersey with the letter C printed on the front. There are sawhorses, wire and wooden fencing, trees, a hill, a wide building with an unfinished roof, and elaborate windows and chimneys (perhaps a dormitory?) in the background. There is also a person wearing a hat behind the wire fencing, facing the camera.